2019
DOI: 10.4236/aid.2019.93015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Patterns and Molecular Characterization of <i>Klebsiella pneumoniae</i> in Clinical Isolates at Mbarara Regional Referral Hospital

Abstract: Background: Klebsiella pneumoniae is one of the most frequent opportunistic pathogens causing a range of infections and being resistant for beta-lactamases (ESBL) and Carbapenemases. Aim: The aim of the present study was to determine the antimicrobial resistance patterns and molecular characterization establishing the phenotypes and genotypes associated with drug resistance, an antibiogram of genotypically positive isolates for resistance of Klebsiella pneumoniae in clinical isolates at MRRH. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…Klebsiella pneumoniae (Kp) is a Gram-negative opportunistic bacterium, from the Enterobacteriaceae family, which classically produces lobar pneumonia, particularly in immunocompromised patients, and it is known to cause hospital-acquired pneumonia, meningitis, bloodstream, and urinary tract infections [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella pneumoniae (Kp) is a Gram-negative opportunistic bacterium, from the Enterobacteriaceae family, which classically produces lobar pneumonia, particularly in immunocompromised patients, and it is known to cause hospital-acquired pneumonia, meningitis, bloodstream, and urinary tract infections [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urine sample has the highest source of K. pneumoniae in this study is suggestive of urinary tract infections and accounts for almost 40% of nosocomial infections [23]. More so, environmental pressure [15] has been noted as a factor that could be responsible for the variations observed in the recovery of K. pneumoniae from clinical specimens. Klebsiella is the most heat tolerant among all enteric pathogens [24], having maximal specific growth rate at 37˚C and are reported to survive at higher humidity [25].…”
Section: Discussionmentioning
confidence: 61%
“…This finding agrees with previous study by Olowo-okere et al [20] from Sokoto, Nigeria, where they isolated 292 Enterobacteriaceae including K. pneumoniae from clinical specimens and most were recovered from urine specimens [49.0%). Turugurwa et al [15] also reported highest (50.85%) Klebsiella recovery from urine samples irrespective of age and gender in Uganda. Similar findings from other investigators from Uganda reported that urine is the principal source of Klebsiella [21,22].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations